L’injustice épistémique : questions de vérité et méthode - Sénac, Coline (Labyrinth, 2022)
This article proposes the comparison of two methods of analysis, semiotics, and hermeneutics, to address contemporary issues in ethical and political philosophy, through the study of the phenomenon of epistemic injustice. Conceptualized by Fricker (2007), epistemic injustice is synonymous with the denial of the value of knowledge that an individual possesses because of prejudices about the social group to which he or she belongs or is affiliated. When epistemic injustice is studied in the empirical world, it poses some crucial issues in terms of interpreting the meaning that the individual gives to the experience of injustice that he or she experiences. Although the interpretation of injustice is central to the understanding of the phenomenon itself, little research in ethical and political philosophy addresses these aspects, because of the failure to sufficiently mobilize analytical methods such as semiotics and hermeneutics. However, these two methods, usually used in other fields to deal with these aspects, allow us to question the treatment and the interpretative scope of the epistemic injustice by the different interlocutors involved in the interaction in which it is reconducted. The comparison of these two methods in the analysis of epistemic injustice finally allows us to argue in favor of the hermeneutic method, as defined by Gadamer and rethought by Code (2003), to enhance Gadamer's legacy through the analysis of ethical and political issues in human sciences research.